2021
DOI: 10.1111/acel.13333
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CREB‐mediated autophagy by thioperamide ameliorates β‐amyloid pathology and cognition in Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is an age‐related neurodegenerative disease, and the imbalance between production and clearance of β‐amyloid (Aβ) is involved in its pathogenesis. Autophagy is an intracellular degradation pathway whereby leads to removal of aggregated proteins, up‐regulation of which may be a plausible therapeutic strategy for the treatment of AD. Histamine H3 receptor (H3R) is a presynaptic autoreceptor regulating histamine release via negative feedback way. Our previous study showed that thioperamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 107 publications
1
19
0
Order By: Relevance
“…Because of their wide expression in the brain and their role in modulating autophagy by sensing extracellular metabolites, G-protein–coupled receptors emerge as druggable targets in neurodegeneration. Chemical inhibition of H3R (thioperamide) and 5-HT2AR (desloratadine) promotes autophagy by CREB-mediated upregulation of TFEB/ATG7/LAMP1 (in neurons) and SIRT1 (in microglia), respectively, and significantly reduces Aβ levels in the APP/PS1 mouse model [ 49 , 50 ]. Interestingly, allosteric inhibition of mGluR5 by CTEP restarted autophagy and rescued Aβ pathology in male APPswe/PS1ΔE9 mice, but not in their female counterparts.…”
Section: Autophagy-based Therapeutic Strategies For Admentioning
confidence: 99%
“…Because of their wide expression in the brain and their role in modulating autophagy by sensing extracellular metabolites, G-protein–coupled receptors emerge as druggable targets in neurodegeneration. Chemical inhibition of H3R (thioperamide) and 5-HT2AR (desloratadine) promotes autophagy by CREB-mediated upregulation of TFEB/ATG7/LAMP1 (in neurons) and SIRT1 (in microglia), respectively, and significantly reduces Aβ levels in the APP/PS1 mouse model [ 49 , 50 ]. Interestingly, allosteric inhibition of mGluR5 by CTEP restarted autophagy and rescued Aβ pathology in male APPswe/PS1ΔE9 mice, but not in their female counterparts.…”
Section: Autophagy-based Therapeutic Strategies For Admentioning
confidence: 99%
“… 199 Selenomethionine Induction mTOR inhibition A β -incubated PC12 A β injected-mouse Increase cell viability Prevent cognitive deficits 100 μmol/L 6 μg/mL in drinking water 200 Dihydroartemisinin Induction mTOR inhibition SwAPP-N2a SwAPP-SH-SY5Y APPSwe/PSEN1dE9 transgenic mouse Reduce A β and APP levels Improve memory impairment 1 μmol/L 20 mg/kg (Oral administration) 201 Thioperamide Induction CREB-1-mediated autophagy A β -incubated mouse primary cortical neurons APPSwe/PSEN1dE9 transgenic mouse Reduce A β level Ameliorate neuronal loss Prevent cognitive deficits 1 μmol/L 1–5 mg/kg (i.p.) 202 …”
Section: Autophagy Modulators For Ad Therapymentioning
confidence: 99%
“…Wang et al found that thioperamide administration improves cognitive function, lowers neuronal damage, and reduces Aβ pathology in APP/PS1 transgenic (Tg) mice. According to their results, the beneficial effect has been achieved by increasing Aβ clearance by favoring autophagy and lysosomal processing [160].…”
Section: Effects On Cognitive Functions and Neuroplasticitymentioning
confidence: 99%